MicroRNAs Are Involved in the Development of Morphine-Induced Analgesic Tolerance and Regulate Functionally Relevant Changes in Serpini1 - Tapocik, Jenica D.; Ceniccola, Kristin; Mayo, Cheryl L.; Schwandt, Melanie L.; Solomon, Matthew; Wang, Bi-Dar; Luu, Truong V.; Olender, Jacqueline; Harrigan, Thomas; Maynard, Thomas M.; Elmer, Greg I.; Lee, Norman H. (Frontiers in Molecular Neuroscience, 2016)
Long-term opioid treatment results in reduced therapeutic efficacy and in turn leads to an increase in the dose required to produce equivalent pain relief and alleviate break-through or insurmountable pain. Altered gene expression is a likely means for inducing long-term neuroadaptations responsible for tolerance. Studies conducted by our laboratory (Tapocik et al., 2009) revealed a network of gene expression changes occurring in canonical pathways involved in neuroplasticity, and uncovered miRNA processing as a potential mechanism. In particular, the mRNA coding the protein responsible for processing miRNAs, Dicer1, was positively correlated with the development of analgesic tolerance. The purpose of the present study was to test the hypothesis that miRNAs play a significant role in the development of analgesic tolerance as measured by thermal nociception. Dicer1 knockdown, miRNA profiling, bioinformatics and confirmation of high value targets were used to test the proposition. Regionally targeted Dicer1 knockdown (via shRNA) had the anticipated consequence of eliminating the development of tolerance in C57BL/6J (B6) mice, thus supporting the involvement of miRNAs in the development of tolerance. MiRNA expression profiling identified a core set of chronic morphine-regulated miRNAs (miR’s 27a, 9, 483, 505, 146b, 202). Bioinformatics approaches were implemented to identify and prioritize their predicted target mRNAs. We focused our attention on miR27a and its predicted target serpin peptidase inhibitor clade I (Serpini1) mRNA, a transcript known to be intricately involved in dendritic spine density regulation in a manner consistent with chronic morphine’s consequences and previously found to be correlated with the development of analgesic tolerance. In vitro reporter assay confirmed the targeting of the Serpini1 3’-untranslated region by miR27a. Interestingly miR27a was found to positively regulate Serpini1 mRNA and protein levels in multiple neuronal cell lines. Lastly, Serpini1 knockout mice developed analgesic tolerance at a slower rate than wild-type mice thus confirming a role for the protein in analgesic tolerance. Overall, these results provide evidence to support a specific role for miR27a and Serpini1 in the behavioral response to chronic opioid administration and suggest that miRNA expression and mRNA targeting may underlie the neuroadaptations that mediate tolerance to the analgesic effects of morphine.